QUALITY DEVELOPMENT MANAGEMENT IN IMPROVING THE COMPETITIVE ADVANTAGE OF PRIVATE VOCATIONAL SCHOOLS IN JAMBI PROVINCE - Lidya Triani; Lias Hasibuan; Kemas Imron Rosyadi (Yayasan Literasi Kita Indonesia, 2021)
This study aims to find a profile of Quality Management Implementation in three Private Vocational High Schools with a detailed aim of finding an implementation model to provide information to all other private vocational high schools that have not achieved “A” accreditation so that they can achieve “ A “ accreditation. This research is a qualitative research, where the reseach is conducted in three private vocational high schools in Jambi city which are accredited “A” represented in Yadika, PGRI 2, Pelita Raya schools. Data collection techniques using observation, interview and documentation, data Analysis using the Cresweel model and data valiidity techniques using data triangulation. The results of the research on Implementation of Quality Development Management at private vocational high schools in the form of innovative ideas that are applied in the field, cover a number of aspects that are quite broad because the customers of a Bujan scholl are only students but also administrative staff, teachers, and stakeholders or the community. The Conclusion of this study is that the Quality development management in Increasing the Competitive Advantage of Private vocational high schools in Jambi Provinces is the existence of a solid and responsible team commitment and cooperation in order to get special attention from the community and become an option for the community, the success factor of the Implementation of Quality development management, what can increase competitive advantage in private vocational schools in Jambi Province is organized management, supported by reliable human resources, good relations with the enviroment and the world of work, mature leadership policies, support from foundations and a solid work plan.